Implementation of Clustering Using Representative (CURE) Method for Segmenting Telephone Call Behavior as a Basis for Policy Making by Telecommunication Providers - Andriani, Tuti (Cattleya Darmaya Fortuna, 2024)
The quality of service provided by telecommunication providers is critical to ensure competitiveness in a competitive market. This quality often depends on the policies taken by the provider, which must be based on factual data to avoid decisions that deviate from field conditions. One resource that can be utilized is customer phone call data, which can be analyzed and grouped to understand call behavior. This study aims to implement the Clustering Using Representative (CURE) method in segmenting phone call behavior. The CURE method was chosen because of its ability to find clusters of various shapes and sizes, even when key attributes have low contributions. The test results show that this method is able to produce clusters with a high average percentage of accuracy. Thus, the CURE method is proven to be effective for segmenting phone call behavior, providing a strong foundation for telecommunication providers to make strategic decisions, such as tariff adjustments, loyalty programs, and customer retention strategies.